1970
DOI: 10.3758/bf03329086
|View full text |Cite
|
Sign up to set email alerts
|

Plug fate in the copulatory behavior of rats

Abstract: Normative data on the fate of ejaculatory plugs were collected following a total of 162 ejaculations attained by 18 male rats each given three tests. Sixty -nine percent of the plugs were dislodged, 82% of these after three or fewer intromissions. Males ate a total of 65% of the plugs, whereas females ate none. More than half of the plugs consumed were consumed between the time of dislodging and the next intromission. Plug consumption is a behavioral pattern appropriate for further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Multiple intromissions thus prepare the female tract for effective insemination. That intromissions are effective in this respect is suggested by the data of Mosig and Dewsbury (1970) on laboratory rats. Sixtynine percent of 162 copulatory plugs were removed by subsequent copulation; 82% of these were removed after only three or fewer intromissions (see also Lisk, 1969;Matthews & Adler, 1977).…”
mentioning
confidence: 84%
“…Multiple intromissions thus prepare the female tract for effective insemination. That intromissions are effective in this respect is suggested by the data of Mosig and Dewsbury (1970) on laboratory rats. Sixtynine percent of 162 copulatory plugs were removed by subsequent copulation; 82% of these were removed after only three or fewer intromissions (see also Lisk, 1969;Matthews & Adler, 1977).…”
mentioning
confidence: 84%
“…Other studies demonstrated that the copulatory plug is not effective at preventing insemination by second males, including studies in rats (Lanier et al, 1979), Syrian hamsters (Oglesby et al, 1981), and deer mice (Dewsbury, 1988). Furthermore, both females and males of some species can remove copulatory plugs with apparent ease (Mosig and Dewsbury, 1970;Milligan, 1979;Wallach and Hart, 1983;Fenton, 1984;Koprowski, 1992;Parga, 2003), further complicating the interpretation of its function as a means to enforce chastity.…”
Section: Molecular Reproduction and Developmentmentioning
confidence: 99%
“…Ejaculations are usually preceded by a variable number of intromissions, whereby the penis enters the vagina but no sperm are transferred (Dewsbury 1984). In rats, such behaviour removes copulatory plugs from previous males, and morphological features such as penile spines may facilitate such removal (Mosig & Dewsbury 1970). However, it is not clear whether these mating characteristics represent adaptation to a system of multiple mating.…”
Section: Introductionmentioning
confidence: 99%